(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This article analyzes the theoretical and practical aspects of developing students’ coordination abilities through the sport of badminton. During the pedagogical experiment, changes in indicators of coordination, reaction speed, balance, and movement precision were studied using special badminton exercises. The results obtained showed that badminton training is an effective tool for developing coordination qualities.